Autoimmune Pancreatitis and Immunoglobulin G4-related Sclerosing Cholangitis: Past, Present, and Future - Sung-Hoon Moo; Myung-Hwan Kim (The Korean Journal of Gastroenterology, 2022)
The emergence of glucocorticoid-responsive autoimmune pancreatitis (AIP) and IgG4-related sclerosing cholangitis (IgG4-SC), a new disease entity, has attracted considerable interest within the international gastroenterology community. The typical manifestations of AIP/IgG4-SC are obstructive jaundice and pancreatic enlargement in the elderly, which may mimic the presentations of pancreatobiliary malignancies. The timely diagnosis of AIP/IgG4-SC can lead to adequate glucocorticoid treatment, whereas a misdiagnosis can result in unnecessary major surgery. The diagnostic criteria used to diagnose AIP include several cardinal features of AIP that can be detected via pancreatic parenchymal imaging, ductal imaging, serum IgG4 levels, histopathology, other organ involvement, and response to glucocorticoid therapy. The differential diagnosis of AIP/IgG4-SC may include pancreatobiliary malignancies and primary sclerosing cholangitis. Although most patients with AIP/IgG4-SC respond well to glucocorticoid therapy, there is a frequent relapse of the disease in the long term. This review describes the evolution of the concept of AIP and IgG4-related disease, including the development of diagnostic criteria, discusses the current practice for diagnosis and treatment, and suggests prospects for research.